Assessment of hydroclimatic variability and aridity trends in the Mississippi River Basin using parametric and non-parametric techniques - Abeysinghe, Umanda; Balkissoon, Sarah; Aloysius, Noel (Frontiers in Climate, 2025)
The Mississippi River Basin (MRB) has undergone substantial hydroclimatic changes due to climate variability and anthropogenic influences. These changes present challenges for sustainable water resource management and agricultural planning, necessitating comprehensive assessments of climate-driven trends. This study examined spatiotemporal trends in precipitation, potential evapotranspiration (PET), air temperature, and aridity indices across the MRB from 1980 to 2019. Daily meteorological data were obtained from the North American Land Data Assimilation System (NLDAS). Trend detection employed both parametric (linear regression) and non-parametric (Mann-Kendall and Pettitt’s tests) methods, applying a 5% significance level to ensure statistical robustness against non-normality and outliers. Statistically significant increasing trends were observed in PET (+4.18 mm/year in Arkansas, p < 0.001) and temperature (+0.078°C/year in Ohio-Tennessee, p < 0.001). Precipitation trends displayed spatial heterogeneity, with significant increases in the Upper Missouri (+1.91 mm/year, p = 0.03) and non-significant declines in the Lower Mississippi (−0.77 mm/year, p = 0.75). Change point analysis indicated abrupt shifts in PET and temperature in the early 2000s and in precipitation in the late 1990s. Aridity indices (UNEP and De Martonne) revealed significant increases in aridity in the southern and western MRB (p < 0.05), suggesting heightened drought risk. The analysis highlights a clear intensification of hydroclimatic extremes across the MRB. The spatial variability in trends and abrupt changes underscores the need for region-specific adaptive water management strategies to bolster resilience against future climate variability.